Normal human immunoglobulin G4 is bispecific: it has two different antigen-combining sites. - Schuurman, J; Van Ree, R; Perdok, G; Van Doorn, H; Tan, K; Aalberse, R (1999)
Unlike other immunoglobulin G (IgG) subclasses, IgG4 antibodies in plasma have been reported to be functionally monovalent. In this paper we show that the apparent monovalency of circulating IgG4 is caused by asymmetry of plasma IgG4. A large fraction of plasma IgG4 molecules have two different antigen-binding sites, resulting in bispecificity. Sera from patients with IgG4 antibodies to both house dust mite and grass pollen induced cross-linking of Sepharose-bound grass pollen antigen to radiolabelled house dust mite allergen Der p I. This bispecific binding activity was not observed in sera with IgG4 antibodies to either grass pollen or house dust mite exclusively. Depletion of IgG4 antibodies resulted in disappearance of the bispecific activity. By size exclusion chromatography we excluded the possibility that bispecific activity was caused by aggregation of IgG4 antibodies. These results indicate that circulating (polyclonal) IgG4 antibodies have two different antigen-binding sites and therefore are functionally monovalent antibodies.